Pendekatan SAVI terhadap Hasil Belajar Peserta Didik Pembelajaran PAI di SMAN 15 Bandar Lampung - Anna Dia; Chairul Amriyah; Era Octafiona (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Education in the information era demands learning innovations to overcome the dominance of lecture-based methods, which tend to make students passive. At SMAN 15 Bandar Lampung, it was found that 51% of students had not achieved the minimum mastery criteria in Islamic Religious Education (PAI) due to the use of a teacher-centered approach. This study aims to examine the effectiveness of the Somatic, Auditory, Visual, Intellectual (SAVI) approach on students’ learning outcomes in the material The Essence of Loving Allah SWT, Khauf, Raja’, and Tawakal. The research employed a quantitative experimental method using a Quasi-Experimental Non-Equivalent Control Group Design. The research population consisted of all Grade X students (N = 315), with samples taken from class X.E 4 (n = 33) as the experimental group and class X.E 5 (n = 34) as the control group, selected through cluster random sampling. Research instruments included an objective test measuring cognitive skills at level C4 (analysis) and an observation sheet of learning activities. The results showed a significant improvement in the experimental group, with an average post-test score of 90.56 compared to 84.60 in the control group. N-Gain analysis indicated a score of 68.93 for the experimental group (moderately effective category) and 51.19 for the control group (less effective category). The study concludes that the SAVI approach is effective in improving PAI learning outcomes because it integrates students’ physical, sensory, and intellectual potentials in a comprehensive manner.